2017
DOI: 10.1016/j.pcl.2017.06.003
|View full text |Cite|
|
Sign up to set email alerts
|

Transfusion Decision Making in Pediatric Critical Illness

Abstract: SYNOPSIS There are three key issues relating anemia and transfusion: 1) anemia may be well tolerated by patients with physiologic reserve, 2) donor red blood cell physiology is impaired compared to that for native red blood cells, and 3) patients transfused for indications other than anemia attributable oxygen delivery failure have worse outcomes than those who are not transfused. Current approaches to transfusion decision-making (TDM) lack the ability to: 1) differentiate between patients who require transfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 180 publications
(68 reference statements)
1
11
0
Order By: Relevance
“…24 Furthermore, critically ill children transfused for other indications than anemia have worse outcomes than those not transfused with a similar degree of anemia. 26 Most patients (56.7%) received only a single blood transfusion, indicating that acute anemia was the most common reason for blood transfusion, this finding is comparable to reports from Venezuela (86.4%), 27 UK (74%), 23 and USA (69%). 20 Repeated transfusions may increase the risk of alloimmunization, particularly in sickle cell disease and thalassemia patients, therefore extended blood group sub-typing is strongly recommended.…”
Section: Discussionsupporting
confidence: 75%
“…24 Furthermore, critically ill children transfused for other indications than anemia have worse outcomes than those not transfused with a similar degree of anemia. 26 Most patients (56.7%) received only a single blood transfusion, indicating that acute anemia was the most common reason for blood transfusion, this finding is comparable to reports from Venezuela (86.4%), 27 UK (74%), 23 and USA (69%). 20 Repeated transfusions may increase the risk of alloimmunization, particularly in sickle cell disease and thalassemia patients, therefore extended blood group sub-typing is strongly recommended.…”
Section: Discussionsupporting
confidence: 75%
“…3 The target and trigger for transfusion are influenced by a multitude of factors which include the type of procedure, remaining postoperative cardiac lesions, current physiologic parameters, anticipated physiologic changes, ongoing bleeding, and the age of the patient. 4 A prospective, observational study of pediatric postcardiac surgical patients in 30 North American hospitals revealed that transfusion practices varied greatly among the studied centers and that the transfusion triggers varied between and within acyanotic and cyanotic patient groups. 5 Blood transfusions have been associated with increased risk of infection, length of intensive care unit (ICU) and hospital stay, duration of mechanical ventilation, and mortality in the pediatric population.…”
mentioning
confidence: 99%
“…In patients for whom no strong recommendation exists (severe PARDS or hemodynamically unstable patients), it would seem best not to base a decision to transfuse solely on Hb level but rather to factor in other clinical and physiological parameters that might indicate low DO 2 , e.g., elevation of lactate level, low central venous oxygenation, or low near infrared spectroscopy (NIRS) level (56). If there is no evidence of low DO 2 , it is likely that a restrictive transfusion strategy is safe.…”
Section: Existing Evidence Regarding Transfusion and Outcome In Children With Pardsmentioning
confidence: 99%